Role of ultrasound in diagnosis and differentiation of benign and malignant ovarian mass: A Hospital based study in Western Nepal - KC, Subash; Shrestha, Ashish; Khadka, Sagar; Poudel, Ramesh (Asian Journal of Medical Sciences, 2019)
Background: As ovarian malignancies are one of the commonest malignancies in female population, timely and accurate diagnosis helps in early treatment resulting in better survival. Ultrasound is easily available diagnostic tool not only to diagnose but also accurately distinguish malignant from benign ovarian masses. Aims and Objectives: To evaluate sensitivity, specificity and accuracy of ultrasound in diagnosing and differentiating benign from malignant ovarian masses in comparison with histopathological findings. Materials and Methods: A prospective study was carried out from August 2015 to August 2018 for a period of 3 years. Total 150 patients with ovarian masses who were operated in our hospital and their final histopathological reports were available, were included in our study. Ultrasound diagnosis and histopathological diagnosis were compared. Results: Sensitivity, specificity and accuracy of ultrasound in diagnosing and differentiating malignant from benign ovarian masses were found to be 78.94%, 98.47% and 88.23% respectively compared with histopathological findings. Conclusion: Ultrasound is very sensitive, specific and accurate in not only diagnosing ovarian mass but also in differentiating malignant from benign entities making it invaluable and important diagnostic tool in evaluation of ovarian masses.